2020
DOI: 10.1089/jop.2019.0143
|View full text |Cite
|
Sign up to set email alerts
|

Topical Triamcinolone Acetonide-Loaded Liposomes as Primary Therapy for Macular Edema Secondary to Branch Retinal Vein Occlusion: A Pilot Study

Abstract: Purpose: To explore safety and therapeutic efficacy of a topical ophthalmic triamcinolone acetonide-loaded liposome formulation (TA-LF) as primary therapy in patients with macular edema (ME) secondary to branch retinal vein occlusion (BRVO). Methods: Twelve eyes of 12 patients with ME secondary to BRVO were exposed to a topical instillation of 1 drop of TA-LF (TA 0.2%) 6 times a day for 12 weeks to evaluate safety and efficacy. Best corrected visual acuity (BCVA) intraocular pressure (IOP), slit lamp examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 84 publications
(93 reference statements)
1
18
0
Order By: Relevance
“…Among these, topical liposomes (LPs) are one of the most promising strategies [19]. In fact, LPs constitute the only topical system to deliver TA into the vitreous area with clinical evidence of its effectiveness [20][21][22]. The vesicle composition of LPs share almost an indistinguishable outer structure with the cell membrane, conferring its ability to transport either hydrophilic or lipophilic drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, topical liposomes (LPs) are one of the most promising strategies [19]. In fact, LPs constitute the only topical system to deliver TA into the vitreous area with clinical evidence of its effectiveness [20][21][22]. The vesicle composition of LPs share almost an indistinguishable outer structure with the cell membrane, conferring its ability to transport either hydrophilic or lipophilic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cell viability was unaffected by TALF. Finally, the microscopic characterization of TALF using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed that TALF is capable of solubilizing large TA crystals into nanoparticles and encapsulating them at the same time [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lipid-based nanocarriers have emerged as promising nanosystems for intraocular drug delivery. For example, topical liposome-based nanosystems have demonstrated, in preclinical and early clinical studies, to be efficient to deliver triamcinolone acetonide (TA) into the vitreous and retina [ 10 , 11 ]. This technological advance in the ophthalmic pharmacology field represents the opportunity to treat multiple inflammatory and neovascular intraocular disorders avoiding or reducing the use of intravitreal injections.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, topical liposomes (LPs) are one of the most promising strategies [19]. In fact, LPs constitute the only topical system to deliver TA into the vitreous with clinical evidence of its effectiveness [20][21][22]. LPs are biocompatible vesicles composed of a phospholipid-bilayer with structural resemblance to cell membrane, which form small spheroids that are able to carry both hydrophilic and lipophilic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, cell viability was unaffected by TALF. Finally, the microscopic characterization of TALF using Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM), revealed that TALF is capable to solubilize large TA crystals into nanoparticles and encapsulate them at the same time [22].…”
Section: Introductionmentioning
confidence: 99%